Effect of a Sleep Intervention on Mental Health Indicators of Adolescents at Risk for Type 2 Diabetes: Preliminary Findings from the Sleep Manipulation in Adolescents at Risk of Type 2 Diabetes (SMART2D) Study - Featherstone, Ryan (Université d'Ottawa / University of Ottawa, 2019)
Background: Many adolescents are not meeting the recommended sleep guidelines. Lack of sleep in adolescents is a major public health concern, since short sleep duration has been associated with an increased risk of chronic diseases such as obesity, type 2 diabetes, cardiovascular disease, and mental health problems. Canadian youth also show a high prevalence of mental health disorders. One segment of the population particularly at risk is those who are at risk for type 2 diabetes. There is currently a lack of experimental sleep studies in this population and knowing how sleep manipulations can impact mental health outcomes is important to inform future intervention strategies. Purpose: To examine how experimental changes in time in bed (decrease and increase by 1.5-hour per night for one week) affect mental health indicators (depression symptoms, mood, and behavioural problems) in adolescents at risk for type 2 diabetes. Methods: A sample of 10 adolescents who were considered to be at risk for type 2 diabetes was recruited. A randomized, counterbalanced, crossover study (within-subjects experimental design) was used. Participants wore an Actiwatch 2 for a total of four weeks, which included a baseline sleep week, an increased sleep week, a decreased sleep week, and a washout period of one week in between. Validated self-report questionnaires were used to measure depression symptoms, mood, and behavioural problems. Results: Preliminary findings showed improvements in depression symptoms, mood, and impact score after increasing time in bed by 1.5-hour per night for one week compared to decreasing time in bed by 1.5-hour. Conclusion: Compared with decreased sleep, adolescents at risk of type 2 diabetes may obtain mental health benefits with sleep extension, even over a short period of time.
Keywords: Mental Health; Diabetes; Adolescents